The Three Stooges festival a special video version - Three Stooges (Comedy team); GoodTimes DVD.; Movietime Inc. Archives (New York : GoodTimes DVD, 2000)
Spans more than thirty years of Stooge-mania including Curly's first film appearance with the trio, rare TV footage, a party with Frank Sinatra, and Moe on a talk show.
Videodisc recording of program produced in 1986.
"A super Stooges spectacular."--Container.
Moe Howard, Larry Fine, Curly Howard, Shemp Howard and Curly Joe DeRita.
DVD ; DVD player required ; standard full frame (1.33:1) ; single layer ; mono ; dolby digital.
Keywords: Three Stooges (Comedy team) -- Drama; Three Stooges films; Comedy films; Comedy television programs